(untitled) (Philology, 2026)
This paper deals with the Arabic Prose of the 1960s and 1970s through an analysis of the novels by Najīb Maḥfūz, Mīkhāʼīl Nuʽayma, Yūsuf al-Qaʽīd and Imīl Ḥabībī who represent different countries, generations and schools of literature. In spite of their thematic and stylistic diversity, the authors are united by a new sensibility related to their common endeavor to get out of the frame of the external plausibility and the literary canons. Thereby, they are able to create a new everyday reality through the strengthening of the artistic convention and rethinking the archaic models in their works.